Conduct problems are associated with accelerated thinning of emotion-related cortical regions in a community-based sample of adolescents. (April 2023) - Albaugh, Matthew D.; Hudziak, James. J.; Spechler, Philip A.; Chaarani, Bader; Lepage, Claude; Jeon, Seun; Rioux, Pierre; Evans, Alan C.; Banaschewski, Tobias; Bokde, Arun L.W.; Desrivières, Sylvane; Flor, Herta; et al.
Highlights: We characterize the association between age-related cerebral cortical change and conduct problems in a large longitudinal, community-based sample of adolescents ( N = 1039). Higher levels of conduct problems were associated with accelerated age-related cerebral cortical thinning. Findings were not meaningfully altered when controlling for alcohol use, co-occurring psychopathology, and socioeconomic status. This work represents the largest study to date of conduct problems and cerebral cortical thickness development. Abstract: Few studies have examined the association between conduct problems and cerebral cortical development. Herein, we characterize the association between age-related brain change and conduct problems in a large longitudinal, community-based sample of adolescents. 1, 039 participants from the IMAGEN study possessed psychopathology and surface-based morphometric data at study baseline ( M = 14.42 years, SD = 0.40; 559 females) and 5-year follow-up. Self-reports of conduct problems were obtained using the Strengths and Difficulties Questionnaire (SDQ). Vertex-level linear mixed effects models were implemented using the Matlab toolbox, SurfStat. To investigate the extent to which cortical thickness maturation was qualified by dimensional measures of conduct problems, we tested for an interaction between age and SDQ Conduct Problems (CP) score. There was no main effect of CP score on cortical thickness; however, a significant "Age by CP" interaction was revealed in bilateral insulae, left inferior frontal gyrus, left rostral anterior cingulate, left posterior cingulate, and bilateral inferior parietal cortices. Across regions, follow-up analysis revealed higher levels of CP were associated with accelerated age-related thinning. Findings were not meaningfully altered when controlling for alcohol use, co-occurring psychopathology, and socioeconomic status. Results may help to further elucidate neurodevelopmental patterns linking adolescent conduct problems with adverse adult outcomes.